A Comparison of 6 Diagnostic Tests for Carpal Tunnel Syndrome Using Latent Class Analysis. (November 2020) - Wang, William L.; Hanson, Timothy; Fowler, John R.
Background: Nerve conduction studies (NCS), ultrasonography (US), Carpal Tunnel Syndrome 6 (CTS-6), Wainner, Lo, and Kamath are clinical diagnostic tools that can be used to diagnose carpal tunnel syndrome (CTS). Latent class analysis (LCA) is a proven statistical technique that can be used to evaluate diagnostic tests in a lack of a reference standard. Given that there is no accepted reference standard, we elected to perform an LCA to evaluate the 6 clinical diagnostic tests.Methods: One hundred eighty-seven wrists were prospectively evaluated by a board-certified hand surgeon using US, the CTS-6, Wainner, Lo, and Kamath. The NCS were performed by an electrophysiologist according to the standards of the American Association of Neuromuscular & Electrodiagnostic Medicine. The LCA was performed to evaluate individual performance and pairwise combinations of the tests.Results: The NCS demonstrated the highest estimated sensitivity of 97%, and the Wainner had the highest estimated specificity of 97%. Alternatively, the Lo had the lowest estimated sensitivity (36%), and NCS had the lowest estimated specificity (40%). When evaluating pairwise combinations, positive US and NCS demonstrated the highest overall sensitivity at 86%, and negative US and NCS had a specificity of 83%.Conclusions: There is no perfect clinical diagnostic test, with the 6 clinical diagnostic tests having differing sensitivities and specificities. Pairwise combinations of the test can be used to complement one another.